2021
DOI: 10.3233/rnn-211148
|View full text |Cite
|
Sign up to set email alerts
|

Structural connectivity changes in the motor execution network after stroke rehabilitation

Abstract: Background: Although quite a very few studies have tested structural connectivity changes following an intervention, it reflects only selected key brain regions in the motor network. Thus, the understanding of structural connectivity changes related to the motor recovery process remains unclear. Objective: This study investigated structural connectivity changes of the motor execution network following a combined intervention of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) and intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
(59 reference statements)
1
9
2
Order By: Relevance
“…There are connections between the anterior portion of the putamen and associated regions exist in the cortex; the posterior portion of the putamen connects to the primary motor cortex and the supplementary motor area 62 . Available evidence suggests that subcortical regions such as the putamen and thalamus are important regulators of fine motor rehabilitation with previously learned movements 63 . Enhanced FCs from the putamen to primary motor regions has been reported in patients with Parkinson's disease 64 and stroke 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are connections between the anterior portion of the putamen and associated regions exist in the cortex; the posterior portion of the putamen connects to the primary motor cortex and the supplementary motor area 62 . Available evidence suggests that subcortical regions such as the putamen and thalamus are important regulators of fine motor rehabilitation with previously learned movements 63 . Enhanced FCs from the putamen to primary motor regions has been reported in patients with Parkinson's disease 64 and stroke 65 .…”
Section: Discussionmentioning
confidence: 99%
“…62 Available evidence suggests that subcortical regions such as the putamen and thalamus are important regulators of fine motor rehabilitation with previously learned movements. 63 Enhanced FCs from the putamen to primary motor regions has been reported in patients with Parkinson's disease 64 and stroke. 65 A resting-state FC study revealed that the increased FC from the contralesional thalamus in patients with supratentorial stroke compared with healthy individuals and was correlated positively with motor improvement at 6-month follow-up.…”
Section: Functional Connectivitymentioning
confidence: 99%
“…Magnetic resonance imaging including functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) are used to elucidate functional and structural features of the brain. In recent years, DTI data, in particular, have been correlated with the improvement of post-stroke paralysis [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Applying a mathematical approach, namely, graph theory, to analysis of DTI data allows greater understanding of the structural neural networks of the brain [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although changes in structural neural networks during recovery from motor paralysis after stroke have been reported [ 27 , 28 ], to the best of our knowledge, only Wanni Arachchige et al [ 24 ] have investigated the impact of LF-rTMS combined with intensive-OT on the structural neural networks in detail. Their study used the same LF-rTMS plus intensive-OT protocol as ours [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation